Orbital Solutions and Absolute Elements of the Massive Algol Binary ET Tauri. (1st November 2016) - Williamon, Richard M.; Dale, Horace; Evavold, Charles L.; Langoussis, Alexander; Fekel, Francis C.; Muterspaugh, Matthew W.; Williams, Stephen; Napier, Kate; Sowell, James R.
Abstract: We acquired differential UBV photoelectric photometry and radial velocities of the relatively bright, understudied, massive Algol binary ET Tau and utilized the Wilson-Devinney (WD) analysis program to obtain a simultaneous solution of these observations. To improve the orbital ephemeris, the V measurements from the ASAS program were also analyzed. Because of the very rapid rotation of the significantly more massive and hotter component (B2/3 spectral class), only radial velocities of the secondary component, which has a ∼B7 spectral class, could be measured. We derive masses of M 1 = 14.34 ± 0.28 M ☉ and M 2 = 6.339 ± 0.117 M ☉ and equal-volume radii of R 1 = 6.356 ± 0.056 R ☉ and R 2 = 11.84 ± 0.10 R ☉ for the primary and secondary, respectively. The secondary is filling its Roche lobe, so the system is semi-detached. The effective temperature of the secondary was held fixed at 15, 000 K, and the primary's temperature was found to be 30, 280 ± 109 K. The system, which has a period of 5.996883 ± 0.000002 days, is assumed to have a circular orbit and is seen at an inclination of 79 .° 55 ± 0 .° 05 .